Pengembangan Frontend Sistem Informasi Pemasaran Properti Berbasis Website Menggunakan Metode UCD (User Centered Design) - Pebriansyah, Dio; Hidayat, Alfin; Utomo, Agus Priyo (Jurnal Informatika dan Komputer, 2025)
This research discusses the development of a frontend property marketing information system at PT. Total Property, with a focus on developing features so that the system can compete and provide convenience to customers. This research is driven by the need to improve user experience and company competitiveness in an increasingly competitive property industry. The method used is the User-Based Design (UCD) Method, which emphasizes in-depth understanding of user needs and implementation of new features based on user feedback. The KPR feature is specifically integrated to increase convenience and clarity of information for customers looking for property financing. Test results using the Usability Scale (SUS) show a score of 85.4, indicating that users consider this system to be very easy to use and efficient. The implication of this research is the importance of integrating user-focused frontend development to increase company competitiveness in facing dynamic market challenges. In conclusion, developing a property marketing information system with innovative features such as KPR not only improves customer experience but also increases operational efficiency and competitiveness of PT. Total Property in a competitive property market.